A numerical investigation of mechanical response of unfilled styrene butadiene rubber by static straight blade indentation / B. Setiyana...[et al.] - B., Setiyana; R., Ismail; J., Jamari; D.J., Schipper (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This study investigates the mechanical response of straight blade indentation on Unfilled Styrene Butadiene Rubber by Finite Element Analysis (FEA). The mechanical responses investigated were stiffness, maximum stress and indentation load. The rubber material was modeled as a hyperelastic material with the Money-Rivlin Strain Energy Function. Results were presented as a function of the blade characteristics, wedge angle and tip radius at a specified depth of indentation. Results showed that the stiffness and indenter load increase due to an increase in the wedge angle and the tip radius, on the other hand, the maximum stress decreases. Surprisingly, an approximately linear relationship between the mechanical response and the blade characteristic was found. Furthermore, the mechanical response at a specified maximum stress was also discussed.